Advantage and Limitation of Using a Visual Feedback Device during Cardiopulmonary Resuscitation Training. Issue 1 (8th February 2020) - Kim, Chan Woong; Oh, Je Hyeok
Abstract: Introduction: Recent cardiopulmonary resuscitation (CPR) guidelines recommend the use of CPR prompt/feedback devices during CPR training because it can improve the quality of CPR. Problem: Chest compression depth and full chest recoil show a trade-off relationship. Therefore, achievement of both targets (adequate chest compression depth and full chest recoil) simultaneously is a difficult task for CPR instructors. This study hypothesized that introducing a visual feedback device to the CPR training could improve the chest compression depth and ratio of full chest recoil simultaneously. Methods: The study investigated the effects of introducing a visual feedback device during CPR training by comparing the results of skill tests before and after introducing a visual feedback device. The results of skill tests from 2016 through 2018 were retrospectively reviewed. The strategy of emphasizing chest compression depth was implemented during the CPR training in 2017, and a visual feedback device was introduced in 2018. The interval between the CPR training and skill tests was seven days. Feedback was not provided during the skill tests. Results: In total, 159 students completed skill tests. Although the chest compression depth increased significantly from 50 mm (42–54) to 60 mm (59–61) after emphasizing chest compression depth ( P < .001), the ratio of full chest recoil decreased simultaneously from 100% (100–100) to 81% (39–98; P < .001). The ratio of full chest recoil increased significantly from 81% (39–98) to 95% (77–100) after introducing a visual feedback device ( P = .018). However, the students who did not achieve 80% of the ratio of full chest recoil remained significantly higher than in 2016 (1% in 2016, 49% in 2017, and 27% in 2018; P < .001). Conclusions: Although introducing a visual feedback device during CPR training resulted in increasing the ratio of full chest recoil while maintaining the adequacy of chest compression depth, 27% of the students still did not achieve 80% of the ratio of full chest recoil. Another educational strategy should be considered to increase the qualities of CPR more completely.